Analysing wind power penetration in hybrid energy systems based on techno-economic assessments. (October 2022) - Wimalaratna, Yuhani Pamodha; Afrouzi, Hadi Nabipour; Mehranzamir, Kamyar; Siddique, Md Bazlul Mobin; Liew, San Chuin; Ahmed, Jubaer
Abstract: Wind is an environmentally friendly energy source that can be harnessed as an on-shore and off-shore resource. Wind energy, combined with other renewable energy systems, has resulted in a more reliable, feasible, and efficient stand-alone system, known as a hybrid renewable energy system, in which excess energy is stored in batteries. To make hybrid renewable energy systems more efficient using economical energy storage, even in off-grid mode, various other energy combinations have been implemented. In analysing the various combinations of hybrid renewable energy systems, economic factors, such as fuel cost, cost of energy, net present cost, and capital cost, as well as technical factors, namely duty factor, excess energy, average energy production, and unmet load, are considered. The consideration of both economic and technical factors provides comprehensive guidance in determining the optimum load combination, storage type and capacity, off-grid and on-grid simulation details, energy balancing, scale of optimum production, risk assessments, and investor confidence. Accordingly, the operation of hybrid renewable energy systems has improved and become more reliable. Furthermore, the improvement of hybrid renewable energy system performance owing to techno-economic assessments has significantly reduced the costs of battery energy storage used in hybrid renewable energy systems as a backup system. In addition, such improvements in hybrid renewable energy system operation have enabled enhanced applications of these systems in the off-grid mode and resulted in the reduction of high grid upgrading and extension costs in various locations. Hybrid renewable energy systems facilitate the economical distribution of distributed electricity generation in various isolated areas with low density. The analytical methods described in the literature cover various aspects and factors considered in the techno-economic assessments of hybrid renewable energy systems in several countries. This study reviews the penetration of wind power into hybrid renewable energy systems as a solution to current energy deficiencies in different countries around the world. The review is conducted based on the available technical and economic factors of different countries to analyse the wind power penetration in various hybrid systems. Asian countries are noted to have the potential to penetrate wind energy into hybrid systems, yet some constraints, such as lack of experience and information, are a major limitation. Furthermore, in European countries, curtailment, high -wake effects, and financial difficulties are common. The technical development of wind power is insufficient in African countries. European countries are ahead in terms of the technical development of wind power penetration into hybrid systems. In some developed countries, such as Germany, hydrogen is used for energy storage, while batteries and generators are used in most Asian countries. In European, Asian, and North and South American countries, the solar/wind combination was identified as economical whereas photovoltaic and diesel/wind were in African countries. Despite these challenges, almost all countries have identified the potential for wind power generation using the available wind energy resources.